I came across a solved exercise regarding Signals and Systems in which there is a system with impulse response \$h(n)=u(n)\$ and input \$x(n)=u(n)\$. The goal was to find the output of that system (unit step response).

(Note that \$u(n)\$ is the unit step)

So the solution begins saying that the output is the convolution between the input and the impulse response which is:

$$y(n)=x(n)\ast h(n)=\sum_{m=-\infty}^{\infty}x(m)\cdot h(n-m)=\sum_{m=0}^{n}1=n+1$$

After that the solution concludes that the output is:

$$y(n)=(n+1)\cdot u(n)$$

Everything is really elementary and I probably miss something here but how does the term \$u(n)\$ appeared in the output? Wasn't proved that the output is \$n+1\$?

Exectly the same happens in another one concerning a system with \$x(n)=h(n)=a^{n} \cdot u(n)\$ where although \$y(n)=a^{n}\cdot (n+1)\$ the result eventually is said to be \$y(n)=a^{n}\cdot (n+1)\cdot u(n)\$.


When they say:

$$y(n)=x(n)\ast h(n)=\sum_{m=-\infty}^{\infty}x(m)\cdot h(n-m)$$

they are correct, but in the next passage they oversimplify a bit.

Let's do it step by step:

\begin{align*} &\sum_{m=-\infty}^{\infty}x(m)\cdot h(n-m) = \sum_{m=-\infty}^{\infty}u(m)\cdot u(n-m) = \\ &= \sum_{m=0}^{\infty} 1 \cdot u(n-m) = \sum_{m=0}^{\infty} u(n-m) \\ \end{align*}

The function to be summed is \$u(n-m)\$, which is equal to 1 if and only if \$n-m>0 \Leftrightarrow m < n\$.

Since the sum is carried out only for \$m>=0\$, if \$n>=0\$ the result is actually \$n+1\$, but if \$n<0\$ the result is 0, therefore they should have written:

\[ \sum_{m=-\infty}^{\infty}x(m)\cdot h(n-m) = (n+1)u(n) \]


The following image may help:

enter image description here

the red dots are the function values, the green shaded area highlights the value range that will be summed. The image was drawn with \$n = 3\$. You may infer that if \$n<0\$ the green area will disappear, indicating there is nothing to sum.


u(n) is like the Heaviside function in Laplace, it ensures that y(n)=0 for n<0, which must be the case. If you just wrote y(n)=n+1, then y(n) would have negative values for negative n


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.